Effect of Some Antioxidants and Biochemical Parameters on Iraqi Patients Undergoing Regularly Peritoneal Dialysis - Murtadha, Nawal Abdullah; AL- Shammaree, Shatha Abdul Wadood (American Journal of Biomedicine and Pharmacy, 2025)
Increased free radical species is one of the most prevalent problems in patients with chronic renal failure (CRF) receiving peritoneal dialysis (PD), which causes a variety of biochemical abnormalities, including anemia. The present research aimed at contrasting the actions of antioxidants such as superoxide dismutase (SOD), paraoxonase (PON1), and ferritin levels with oxidative stress markers such as malondialdehyde (MDA), nitric oxide (NO), and uric acid (UA), as well as levels of some biochemical variants such as blood glucose, blood urea (BU), creatinine (Cr), erythropoietin (EPO), hemoglobin (Hb), iron (Fe), and total iron binding capacity (TIBC), while body mass index (BMI) and creatinine clearance (CrCl) were calculated. The 124 participants in this study were included; 64 patients with CRF under PD, and 60 apparently healthy subjects, sex/age-matched representing the control group. This study found a substantial drop (P < 0.05) in PON1 and SOD activity, as well as levels of Hb, Fe, TIBC, EPO, and CrCl levels in PD patients versus healthy controls. Patients showed significantly higher amounts of serum ferritin, BU, sCr, MDA, NO, UA, and BU/sCr ratio compared with controls (P < 0.05). The results showed a substantial increase (P<0.05) in the blood glucose level. Conclusion: Serum paraoxonase PON -1 activity is more typically altered than other biochemical markers in peritoneal dialysis patients. Anemia is a common and frequently early consequence of chronic kidney disorders.